2013
DOI: 10.1007/s00259-013-2450-7
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of treatment response using FDG PET performed on day 21 of chemoradiotherapy in patients with oesophageal squamous cell carcinoma. A prospective, multicentre study (RTEP3)

Abstract: This prospective, multicentre study performed in a selected population of patients with oesophageal squamous cell cancer demonstrates that the parameters derived from baseline PET₁ are good predictors of response to CRT. Specifically, a high TV and TLG are associated with a poor response to CRT at 3 months and 1 year, and a high SUVmax is associated with a poor response to CRT at 1 year. FDG PET performed during CRT on day 21 appears to have less clinical relevance. However, patients with a large functional TV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 39 publications
3
24
2
Order By: Relevance
“…This is an important result for the robustness and future development of these tracers in nuclear medicine. Similar results were previously shown by our group for the reproducibility of 18 F-FDG PET images in a series of patients with squamous cell esophageal carcinoma (20). This study clearly demonstrated the lack of reproducibility by physicians of the delineation of hypoxic or proliferative tumoral volumes on PET/CT images.…”
Section: Discussionsupporting
confidence: 77%
“…This is an important result for the robustness and future development of these tracers in nuclear medicine. Similar results were previously shown by our group for the reproducibility of 18 F-FDG PET images in a series of patients with squamous cell esophageal carcinoma (20). This study clearly demonstrated the lack of reproducibility by physicians of the delineation of hypoxic or proliferative tumoral volumes on PET/CT images.…”
Section: Discussionsupporting
confidence: 77%
“…One retrospective multi-center study demonstrated that the MTV defined by a physician significantly decreased from PET1 (pre-CRT) to PET2 (3 weeks from the start of CRT), whereas the MTV defined as 40% of the SUV max did not decrease significantly (25). The MTV from PET1 or PET2 was significantly lower in patients with CR at 3 months, while the SUV max was not.…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, no ongoing trials have been launched using the TMTV to guide therapy. Even if the prerequisite for this type of trial is quality control, as done using various existing control systems (7,19,20), it is anyway required for good PET clinical practice. The main problem is which TMTV technique measurement should be chosen because there is no established consensus.…”
Section: Discussionmentioning
confidence: 99%